Efficiency of Productive Zakat Distribution in Efforts to Improve Mustahik Welfare: A Study at Laznas Daarut Tauhiid Peduli Metro Branch - Mukhlishin , Ahmad; Ritonga, Anas Habibi; Galih Pandu (Sekolah Tinggi Ilmu Syrari’ah Daru ‘Ulum (STSDU) Lampung Timur., 2021)
Poverty reduction efforts and economic empowerment of the poor are carried out through the Dompet Peduli ummah Daarut Tauhiid (DPU-DT) program although it has not yet fully touched all groups of the poor, but this effort is very meaningful in building a strong foundation for the development of the Dompet Peduli Ummah-Daarut Tauhiid program to wider area and cover more targets. This research is a field research using a qualitative descriptive approach. The primary data sources in this study were the branch heads, managers and mustahik of LAZNAS Daarut Tauhiid Peduli Metro Branch. Data collection procedures were carried out through interviews, observation, and documentation. Data analysis includes data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the distribution of productive zakat at LAZNAS Daarut Tauhiid Peduli Metro Branch in 2020 was carried out in various ways, namely by conducting field surveys, serving submissions, and public complaints. The distribution of productive zakat at LAZNAS Daarut Tauhiid Peduli Metro Branch is efficient and can improve the welfare of mustahik. This can be seen from the fulfillment of clothing and food needs, there is no dependence on productive zakat because they already have a job, have a steady income and can support their dependents.